Optimal design of the gas storage surface pipeline system with injection and withdrawal conditions - Jun Zhou; Liuling Zhou; Guangchuan Liang; Shaobo Wang; Tiantian Fu; Xuan Zhou; Jinghong Peng (Petroleum, 2021)
Underground natural gas storage (UNGS) is an important part of the natural gas supply system to ensure a balanced energy supply. The surface system, as an important part of the gas storage, undertakes the functions of gas injection and gas production of the gas storage, and its investment economy is of vital importance. In fact, the UNGS surface pipeline network has two-way injection and production characteristics, which is different from the one-way production characteristics of conventional oil&gas gathering and transportation systems. This paper takes the minimum investment of the pipeline network as the objective function, considers the gas injection and gas withdrawal flow conditions and esablishes a mixed integer non-linear programming model (MINLP) for the surface pipeline network of the UNGS to optimize its pipeline layout and diameter parameters. Constraints including the well affiliation, the number of stations, the gathering radius, the processing capacity and the flow/pressure equilibrium equations, are also taken into consideration. Taking an UNGS in China as an example, the results of the optimal structure and diameter of the pipeline network, as well as the pipe flow, node pressure, and maximum/minimum flowrate during gas injection and gas withdrawal are obtained. Finally, the effects of constraints such as processing capacity and radius on the structure layout and investment of the UNGS are analyzed, verifying the reliability and effectiveness of the model.